2022
DOI: 10.1186/s40359-022-00875-9
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for a randomized controlled trial of the Men in Mind training for mental health practitioners to enhance their clinical competencies for working with male clients

Abstract: Background Although the proportion of men seeking professional mental health care has risen over the past two decades, on average, men continue to attend fewer sessions of psychotherapy and are more likely to drop out of treatment prematurely compared to women. Men account for three-quarters of suicide deaths; furthermore, over half of the males who die by suicide have engaged with mental health care in the 12 months prior to their death. These findings highlight a need to equip mental health p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…This study was a single-blind RCT, with two parallel groups: the active intervention group (Men in Mind) and a wait-list control. The full methodology has been described in detail elsewhere (Seidler, Wilson, Toogood, Oliffe, et al, 2022). All data were collected online, and ethical approval was obtained from The University of Melbourne’s Psychology, Health, and Applied Sciences Human Ethics Subcommittee (ID: 22618).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was a single-blind RCT, with two parallel groups: the active intervention group (Men in Mind) and a wait-list control. The full methodology has been described in detail elsewhere (Seidler, Wilson, Toogood, Oliffe, et al, 2022). All data were collected online, and ethical approval was obtained from The University of Melbourne’s Psychology, Health, and Applied Sciences Human Ethics Subcommittee (ID: 22618).…”
Section: Methodsmentioning
confidence: 99%
“…There is also evidence of practitioner subgroup effects, particularly in relation to gender. For example, female practitioners often report difficulties in engaging male clients (Sweet, 2012), as some perceive the therapeutic alliance as precarious due to the lack of shared experience of masculine gender socialization, leading to reduced self-reported competence when working with men (Seidler, Wilson, Toogood, Oliffe, et al, 2022). Therefore, the mismatch between masculinity and therapy may be exacerbated in instances where female practitioners work with male clients; however, this requires further investigation.…”
mentioning
confidence: 99%
“…Taken together, our results showed that a large proportion of men who dropped out of therapy did so because they found it unhelpful or were dissatisfied with the therapeutic methods. This underscores the necessity for enhancing mental health services by adopting a person-centered and gender-sensitive approach specifically tailored to men, as has already been discussed by experts in the field (American Psychological Association Boys and Men Guidelines Group, 2018;Seidler et al, 2019Seidler et al, , 2022. Moreover, as also discussed by Seidler et al (2021), some dropouts from therapy might be considered an inevitable consequence of men trialing their connection with a range of practitioners before finding the right 'fit'.…”
Section: Psychotherapy Dropout In Men and Tmi 12mentioning
confidence: 81%
“…For future translation of these review findings into practice, service delivery interventions could look similar to the “Men in Mind” gender competency-based training curricula, which was developed, in part, from the scoping review of approaches by Seidler, Rice, Ogrodniczuk, et al (2018) for optimally engaging men in psychological treatment. This review informed the design of a world-first randomized controlled trial that validated the training for mental health professionals (Seidler et al, 2023). While developed for mental health service contexts, the core tenets of “Men in Mind” are likely relevant to all healthcare settings serving men and reflect many of the core findings of this review.…”
Section: Discussionmentioning
confidence: 99%